2003
DOI: 10.1590/s0036-46652003000400011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IgG antibodies specific to Toxoplasma gondii among blood donors in Recife, Northeast Brazil

Abstract: SUMMARYA serological survey of Toxoplasma gondii infection in blood donors was carried out in order to identify seroprevalence in Recife, Brazil. Sera from 160 individuals (119 male and 41 female) were evaluated by using a Toxoplasma IgG-antibody enzyme immunoassay (Denka Seiken Co., LTD., Tokyo, Japan). The seropositive percentual for males (79.0%) showed to be higher (p ≤ 0.05) than for females (63.4%). This percentage increases with age, ranging from 18.2% to 92.6% for individuals aging under 20 and 40-50 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
37
3
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 12 publications
17
37
3
10
Order By: Relevance
“…These observations agree with previous studies that indicate a percentage of IgG anti-T. gondii antibodies in the Brazilian population (20,(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 93%
“…These observations agree with previous studies that indicate a percentage of IgG anti-T. gondii antibodies in the Brazilian population (20,(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 93%
“…6 In the present study more than 60% of the pregnant women tested positive for IgG anti-T. gondii antibodies, which is in agreement with other studies carried out in Brazil reporting seropositivity rates ranging from 22.8% to 71.5%. [7][8][9][10][11][12] Two recent studies performed in the northwest region of São Paulo State found rates similar to those reported in the current study. 5,13 Pregnant women at risk of congenital transmission of toxoplasmosis were younger than those without risk.…”
Section: Discussionsupporting
confidence: 91%
“…The factors like nutritional status, sociocultural habits, geographic climatic variations, transmission route, and age will influence the toxoplasmosis seropositivity [31]. One-third of the world's population is affected by the infection caused by this parasite [32,33].…”
Section: Discussionmentioning
confidence: 99%